EDUCATIONAL ACTIVITY IN THE SECOND REPUBLIC OF POLAND. THE OUTLINE OF ISSUES - Siedlaczek-Szwed, Aleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In an ethnically and culturally diversified society, great importance was assigned to education open to tolerance and respect for other people. In this respect, activities of Vilnius associations deserves special distinction, because – in spite of conflicts or differences of opinion – none of the associations propagated nationalist slogans nor promoted negative emotions. The dominating attitude was marked with moral sensitivity, connected with practical introduction of the pupils to perform their social and occupational ways, norms of conduct in compliance with the rules of amicable co-existence, their legacy and the sense of national identity in the spirit of tolerance.The fundamental objectives of the undertaken activities were: reconstructing reasons and circumstances of taking care of minor children, orphaned or deprived of appropriate care executed by their own families, determining the incentives contributing to development of tutelary ideas during the discussed period of time and revealing mechanisms causing development and extension of the activities, evaluating the welfare and educational work against the background of social needs, specification of the criteria to be satisfied by the institutions providing care to children in the environment of the Second Republic.